The Role of Teachers in Building a Positive Classroom Culture: A Study of Classroom Management in the Era of Modern Learning - Nazilah, Elsa Ngatiatun; Hayati, Nurun Nafi’atul; Azizah, Rizka Nur (Proceedings Series on Social Sciences & Humanities, 2025)
In the era of modern education, which is rapidly evolving with technological advancements and new pedagogical approaches, the role of teachers extends beyond merely delivering content. Teachers now serve as facilitators, moderators, and creators of a conducive learning environment. This study aims to explore in depth how teachers can foster a positive classroom culture through effective classroom management strategies. A positive classroom culture supports students’ emotional, social, and academic well-being, fostering mutual respect, a sense of safety, and active student participation in learning. This research employs a descriptive qualitative approach, utilizing interviews, observations, and journal data analysis.The findings indicate that successful teachers in building a positive classroom culture prioritize open communication, implement fair and consistent rules, and provide feedback that creates engaging and relevant learning experiences for students. Furthermore, the appropriate use of educational technology enhances positive interactions between teachers and students. Teachers must understand individual student needs, demonstrate empathy and high levels of care, and maintain flexibility to create a pleasant and inclusive classroom climate. Modeling exemplary behavior and positive attitudes in daily practice is essential, as these serve as references for students to emulate good character and ethics.However, several challenges exist, such as students’ diverse backgrounds, limited facilities and infrastructure, and insufficient teacher training in classroom management. These challenges can be addressed through collaboration among teachers, support from schools, and involvement of students’ families. The study concludes that the success of building a positive classroom culture depends on teachers’ commitment to implementing student-centered classroom management principles and their responsiveness to the dynamics of modern learning. Thus, the classroom becomes not only a place for knowledge transfer but also a space that supports students’ personal development. Modern education requires teachers to adapt quickly in designing learning experiences that focus not only on cognitive aspects but also on affective and social dimensions. Therefore, educators must innovate in classroom management practices to ensure a comfortable, safe, enjoyable, and motivating environment for optimal student growth. This study contributes to the development of classroom management theory and practice in Indonesia and serves as a reference for teachers in fulfilling their roles in the ever-evolving landscape of modern education.